The application of component-based methodology in developing visual power system analysis tool - Nor, K.M.; Gani, T.A.; Mokhlis, Hazlie (IEEE, 2001)
This paper describes the application of component-based methodology in developing a visual power system analysis tool. The component systems are built from public domain codes, commercial components and in-house developed components. Public domain codes and commercial components are reused to handle electrical diagramming, user and database access and analytical computation. Other components such as power system model and analytical analysis are developed in-house. The tool is built by architecting component systems, which play a role in drawing a one-line diagram, capturing database, and performing analysis such as load flow, symmetrical and unsymmetrical faults. By using this approach, a more flexible architecture of power system software consisting self-contained components, placed in independence layer is obtained. Changes in one component will not propagate to others. Therefore, the cost of development is reduced.